Analisis Perbandingan Kinerja Keuangan pada Bank Rakyat Indonesia dan Bank Tabungan Pensiunan Nasional Syariah Periode 2017-2022 - Wirantika, Reny; Awali, Husni (Mabny: Journal of Sharia Management and Business, 2024)
Banks as intermediaries that can help mobilize and channel public funds need to be measured by how successful financial management has been. By knowing its financial performance, we can also find out whether the company is running smoothly or not, and can see its banking and financial prospects. This research was conducted to discuss differences in the financial performance of Bank Rakyat Indonesia and the Sharia National Pension Savings Bank in the 2017-2022 period. This research is a quantitative study with the number of samples studied, namely 24 quarterly financial reports of Bank BRI and Bank BTPN Syariah. Selection of the sample using the saturated sample method. Methods of data analysis using independent sample t-test and Mann-Whitney test analysis. The results showed that there was a significant difference between the financial performance of Bank Rakyat Indonesia and the Sharia State Pension Savings Bank for the 2017-2022 period based on all the financial ratios studied, namely ROA, ROE, BOPO, NPL/NPF, FDR/LDR, NIM/NOM and CAR. The financial performance of the Sharia National Pension Savings Bank is superior to Bank Rakyat Indonesia in terms of the ratios of ROA, ROE, BOPO, NIM/NOM, FDR/LDR NPL/NPF and CAR for the 2017-2022 period.